An Invitation to Sociology of Climate Governance in Sub-Saharan Africa: Concealing the Intersections of Environmental Justice, Inequality, and the Nation State - Mugambiwa, Shingirai Stanely (Technium Social Sciences Journal, 2021)
This paper provides a synopsis of the critical debates in environmental sociology vis-à-vis climate governance and evokes the intersections of environmental justice, equality and the nation state. The nation state, which in this study refers to the government of the day is regarded as an important factor in determining the state of environmental justice and equality. This is because the government has the mandate to formulate and implement policies such as environmental policy. Issues of injustice and inequality are clearly spelt out in the discipline of sociology which provide insights on ways through which humans in societies respond to environmental crises. The paper places considerable emphasis on the political economy of environmental sociology which lies on the effects of modernity and capitalism in relation to socio-ecological well-being of communities. This is significantly linked to Karl Marx’s contribution on class struggles over the means of production which favours the bourgeoisie who are responsible for the greater ecological damage.